Academic Procrastination and Smartphone Addiction Linked to Sleep Quality Decline: Penundaan Akademik dan Kecanduan Ponsel Pintar Berkaitan dengan Penurunan Kualitas Tidur - Eka Putri Agustina; Eko Hardi Ansyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Sleep quality is a fundamental physiological need and a critical determinant of cognitive functioning, emotional regulation, and academic performance among university students. Specific Background: Early adult students frequently encounter academic demands and intensive smartphone use, both of which are associated with disrupted sleep patterns and reduced restorative rest. Knowledge Gap: Previous studies have primarily examined either academic procrastination or smartphone addiction separately, leaving limited empirical evidence on their simultaneous relationship with sleep quality among early adult students in East Java. Aims: This study investigates the relationships between academic procrastination, smartphone addiction, and sleep quality among early adult university students in East Java. Results: Using a quantitative correlational design with 272 students and multiple linear regression analysis, findings indicate significant negative associations between academic procrastination and sleep quality (B = –0.468; p < 0.05) and between smartphone addiction and sleep quality (B = –0.327; p < 0.05). Simultaneously, both variables account for 51.2% of the variance in sleep quality (R² = 0.512; F = 141.224; p < 0.05), demonstrating that higher levels of academic delay and excessive smartphone use correspond with lower sleep quality. Novelty: This study integrates academic procrastination and smartphone addiction within a single regression model to explain variations in student sleep quality. Implications: The findings provide empirical evidence for developing campus-based time management education, digital well-being initiatives, and sleep hygiene programs targeting early adult students. Highlights: Task postponement behavior shows a statistically significant inverse association with restorative rest patterns. Excessive mobile device dependency demonstrates a significant negative relationship with nightly recovery conditions. Combined behavioral factors explain more than half of the variance in student sleep conditions. Keywords:Academic Procrastination; Smartphone Addiction; Sleep Quality; Early Adult Students; Multiple Linear Regression